Fatigue-induced alterations in force production, trajectory and performance in alpine skiing - Chollet, M.; Hintzy, F.; Cross, M. R.; Delhaye, C.; Morel, B.; Monjo, F.; Samozino, P. (Journal of Sports Sciences, 2024)
In giant slalom, the ability to apply a high amount of force in the radial direction is essential for performance. A race is characterized by repeated turns performed at high velocity, potentially inducing fatigue. Therefore, this study aimed to assess the effect of fatigue on performance, trajectory characteristics, and force production capacities onto the snow. Twelve skiers ran a 4-turn section with (FATIGUE) and without pre-induced fatigue (CONTROL). Knee extensor maximal voluntary contraction (MVC) was performed before the experiment and after both conditions. Section time, energy dissipation, path length, total force output, force application effectiveness, and EMG activity of the main lower-limb muscles were compared between conditions. Multiple linear regressions were used to understand whether interindividual variability in the kinematic, kinetic and EMG between conditions explains variability in performance changes with fatigue. MVC was lower after FATIGUE (-19.1 ± 6.4%, p < 0.001) but did not change after CONTROL. FATIGUE was associated with longer section times (+0.21 ± 0.11 s, p < 0.001), energy dissipation (-0.78 ± 1.05 J.s.kg.m-1, p = 0.026), path length (+1.1 ± 1.6 m, p = 0.033) and lower force application effectiveness (-0.1 ± 0.1, p = 0.017). This study experimentally demonstrates that fatigue in giant slalom results in lower force application effectiveness, inducing over-dissipation of mechanical energy and longer path length, leading to lower performance.